Pemberdayaan Pedagang Melalui Penerapan Standarisasi Higiene Dan Sanitasi Makanan - Nisrina Nisrina; Cahaya Cellomita Sembiring; Dinda Tiara Anisha Putri; Hagia Sofiah Siregar; Nasywa Nathania Haqiqi; Nurul Indah Nasution; Riani Asyahra; Salwa Aina Nauli (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Food and drinks sold by vendors located on crowded streets or public places are often enjoyed immediately without the need to know how the process is processed. Hygiene and sanitation is an effort to maintain food hygiene and safety involving the control of various factors from the food itself, food handlers, environmental conditions, and equipment used that can affect health. Snacks sold by food vendors must pay attention not only to their nutritional value, but also to pay attention to hygiene and sanitation. This study used descriptive qualitative methods that involved the use of observation and interview techniques as tools to collect data. This study aims to expand the understanding and skills of food handlers regarding hygiene and sanitation through community empowerment at one of the miso stalls located on Jl. Golf Course, Kp. Tengah, Pancur Batu District, Deli Serdang Regency, North Sumatra. Food handlers should pay attention to personal hygiene, all stages of food production from selection of ingredients to serving, and maintain the cleanliness of the environment around the food processing site in order to improve the cleanliness and quality of the food produced.